Application of HOTS Model Learning through PBL method on Fraction Calculation Operation Material to Improve Students' Counting Skills - Kayadi, Nur (Universitas Sebelas Maret, 2022)
High-level thinking (HOTS or High Order Thinking Skills) must be trained and familiarized early in learning in elementary schools. This is one way to apply learning with the Problem Based Learning (PBL) method, which aims to involve students in tasks that require the use of various levels of thinking to produce children's numeracy skills in the material of fraction counting operations in real life. Learning Mathematics Class V Semester 1 of the 2022/2023 academic year on the material of fraction calculation operations with the problem-based learning model (PBL) has succeeded in providing learning experiences to students in understanding the concept of calculating ordinary and mixed fractions. The whole learning process involves communication and collaboration activities in developing analyzing and thinking skills from the lowest to the highest level. The results of this learning are able to improve numeracy skills and at the same time improve students' communication and collaboration skills. The low ability to adapt and communicate in analyzing in groups as well as the mastery of functional expressions of learners become weaknesses that hinder the continuity of discussions and presentations. Thus, the role of the teacher as a solution provider is still needed.